Clinician prediction survival of end stage non-cancer patients. (1st November 2016) - Thai, V.; Ghosh, Sunita; Tarumi, Yoko; Wolch, Gary; Mayo, Pat; Fassbender, Konrad; Lau, Francis; de Kock, Ingrid; Mirhosseini, Mehrnoush; Quan, Hue
Abstract : Objectives : Single, program wide multi-site prospective study examining the (1) accuracy of non-cancer clinician prediction survival (CPS) by palliative practitioners on 1st assessment. (2) Factors affecting CPS; (3) potential impact on clinical care. Design and methods : Single, program wide multi-site prospective study ( n = 282). CPS was divided into four clinically relevant time periods (≤2 weeks, >2 to ≤6 weeks, >6 to ≤12 weeks, and >12 weeks). Multivariate analysis was done on six predictor variables. Results : More than ½ of patients died before their clinically relevant predicted time periods (of more than 2 weeks). Only one out of the six predictor variables impacted on clinician accuracy on logistic regression and that being the survival prediction time periods. Conclusion : Non-cancer CPS, even by palliative practitioners, remains overly optimistic. This raises the question in that these individuals may have been potentially over-treated.